PENERAPAN NILAI PERSATUAN DALAM SEJARAH DAN PELESTARIAN KLENANG NUNGGAL MAHAPATI DI WILAYAH PANCONG KOPONG SEBAGAI WARISAN BUDAYA - Lestari, Juniar Eva; Wulandari, Mizra; Syaripuddin, Muh.Amir; Tohazri , M.Okviraman; Sabili, M.Mawazi; Rahman, M.Khalilur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to identify the application of Pancasila values in thehistory of the development of Klenang Nunggal Mahapati in the Pacor Kopongarea, identify the contribution of local communities, especially youth, in maintainingand preserving Klenang Nunggal Mahapati in accordance with Pancasila valuesand identify the impact of preserving Klenang Nunggal Mahapati on development.national character based on Pancasila values. Klenang is a traditional musical arttypical of Lombok that uses metal and rubber equipment to produce unique anddistinctive sounds. This music is often played at certain events, such as traditionalcelebrations, religious ceremonies and cultural festivals. The method we used inthis research was observation by direct observation and interviews with klenangartists who are still active. The results of this research show that the application ofPancasila values is very important in the history and preservation of the nunggaklenang, especially the values of unity and consensus deliberation where theexistence of these values can strengthen friendship between members and canproduce joint decisions related to the progress of the klenang this nunggal, apartfrom that, the contribution of the local community, especially youth, plays a veryimportant role in preserving this kelenang, the impact that occurs from preservingthis klenang on the development of national character is that the community bettermaintains culture and also maintains the values of Pancasila in behavior,especially the values of unity and deliberation and consensus in preservingKlenang Nunggal Mahapati as a cultural heritage